Correlation between CRP and IL-6 Serum Levels after Induction of Diabetes and Eight Weeks Resistance Training in Rats - Saeed Ghodsbin (Report of Health Care, 2017)
Introduction: Systemic low-grade chronic inflammation is considered to be one of the significant characteristics of diabetes mellitus. This study aimed to investigate the correlation between C- reactive protein (CRP) and interleukin- 6 (IL-6) serum levels, after induction of diabetes and eight weeks of resistance training in rats. Methods: For the purpose of this experimental study, 24 streptozotocin induced diabetic rats were divided into three groups of 8 including (1) first week diabetic control, (2) last week diabetic control and (3) resistance training. Moreover, 8 healthy rats were chosen as the first week healthy control groups to assess the effects of diabetes induction on CRP and IL-6 serum levels. Rats of group 3 were subjected to an eight-week resistance training (3 days/week). Kolmogorov-Smirnov, independent-samples t-test, and Pearson correlation coefficient, were used for data analysis (p≤0.05). Results: Induction of diabetes had a significant effect on the increased serum levels of CRP (p = 0.01) and IL-6 (p = 0.01). However, after 8 weeks of resistance training, a significant decrease was observed in CRP (p = 0.001) and IL-6 (p = 0.01) serum levels of streptozotocin induced diabetic rats. Also, there was no significant correlation between CRP and IL-6 serum levels, after the induction of diabetes (p = 0.23) and eight weeks of resistance training (p=0.65). Conclusion: It appears that there is no correlation between CRP and IL-6 serum levels, after the induction of diabetes and eight weeks of resistance training in rats.